A Comparative Study of Community Structure and Plankton Abundance in Seaweed Cultivation Areas in Puntondo, Takalar Regency - Rafikah Amalia; Nita Rukminasari; Muh. Tauhid Umar; Irmawati Irmawati (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Healthy tropical coastal waters ideally have a diverse plankton community, which serves as an indicator of optimal ecological stability. Monitoring based on the analysis of plankton community structure is required as a means of detecting changes in the ecological conditions of the waters. Given the scarcity of ecological data in this region, this study aims to analyse the community structure and abundance of plankton in the waters off Puntondo as a basis for coastal ecosystem management. Sampling was carried out at three stations using purposive sampling with a No. 25 plankton net, and the data were analysed using ecological indices and multivariate analyses (nMDS, ANOSIM and SIMPER) via PRIMER version 5. The results showed that the phytoplankton consisted of 12 species dominated by Bacillariophyceae with an abundance of 476–520 ind/L, and the zooplankton consisted of 6 species dominated by Polychaeta with an abundance of 6090–6630 ind/L; there were no significant differences between stations for either group. Moderate diversity, high evenness and low dominance indicate that the plankton community is in a state of equilibrium, reflecting that the waters of Puntondo are still capable of sustaining the plankton ecosystem despite facing anthropogenic pressures that require ongoing monitoring.